Propagação vegetativa do pessegueiro com uso de extrato de estruturas subterrâneas de tiririca (Cyperus rotundus L.) - Rossetti, Joselaine (2015)
The objective of this study was to evaluate the effect of different concentrations of aqueous extract of underground constructions of nutsedge (Cyperus rotundus L.) in herbaceous cuttings and softwood peach of Chimarrita and Chiripá cultivars. The cuttings were collected from mother plants, to obtain the extract were used 50 grams of underground structures for sedge herbaceous cuttings and 100 grams in the extract intended for softwood cuttings. The herbaceous cuttings and softwood remained immersed in the extract for 40 minutes. In herbaceous followed were placed in commercial substrate. As for the softwood cuttings were also packed in commercial substrate and medium sand. The experimental design was completely randomized with arrangement of treatments in a factorial design. They compared the factors concentration of the extract, with levels 0%; 25%; 50%; 75%; 100% to 5 doses, cultivating factor: 2 Chimarrita and Chiripá, with 3 repetitions. Evaluation of rooting occurred after 45 days for softwood cuttings and after 80 days for softwood. We evaluated the results of the response variables: number of shoots, length of shoots, number of leaves, leaf length, number of roots, root length and number of calluses. For qualitative variables: types of cuttings and varieties, the results were subjected to analysis of variance and mean comparison test by Tukey test at 5% error probability. We conclude that the aqueous extract of underground constructions of nut grass L. was not effective in promoting the rooting of herbaceous cuttings and softwood peach cultivars chimarrita and chiripá.